Pemanfaatan Abu Limbah Kayu sebagai Material Subtitusi Sebagian Semen pada Campuran Beton - Imran, Imran; Attamimi, Aqilah; Fajri, Fajri (Portal: Jurnal Teknik Sipil, 2023)
The use of waste to meet the need for environmentally friendly construction materials using the recycling principle is mostly obtained from burning waste which are quite a lot of deposits available. Deposits of wood waste especially from sawmills in furniture industries, are just deposits of waste. However, wood waste ash can be used as a construction material in concrete mixture. This research aims to determine the compressive strength of concrete produced from using wood waste ash with a percentage 15%, 20% and 25% of cement. The research results showed that by substituting some cement using 15% of wood waste ash, the highest compressive strength of concrete was obtained at 8,08 MPa. The reduction in the compressive strength value of concrete is influenced by addition of percentage of wood waste ash, the greater the addition of wood waste ash in the concrete mixture, the smaller the resulting compressive strength value.